2006
DOI: 10.1007/s00109-006-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term hyperthermia prevents activation of proinflammatory genes in fibroblast-like synoviocytes by blocking the activation of the transcription factor NF-κB

Abstract: Fibroblast-like synoviocytes (FLS) play a key role in the genesis of rheumatoid arthritis (RA). FLS are among the most versatile cells with the potential to activate an array of genes that are able to initiate and propagate inflammation in RA-affected joints. Controlling activation of FLS might hold the key to restraining inflammation in RA-affected joints. In this study, we investigate the effect and mechanisms of short-term hyperthermia on a series of proinflammatory genes in FLS. In vitro experiments demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…However, like us, others also demonstrated discrepancies in the time course of HSP70 and/or HO-1 expression and the inhibition of NF-κB mediated by HT (4,6). Similar to our results 4 using FLS, it has been reported that IκB degradation in heat shocked macrophages is blocked for up to four hours (7).…”
Section: Fibroblast-like Synoviocytes (Fls) Play An Important Role Insupporting
confidence: 88%
See 1 more Smart Citation
“…However, like us, others also demonstrated discrepancies in the time course of HSP70 and/or HO-1 expression and the inhibition of NF-κB mediated by HT (4,6). Similar to our results 4 using FLS, it has been reported that IκB degradation in heat shocked macrophages is blocked for up to four hours (7).…”
Section: Fibroblast-like Synoviocytes (Fls) Play An Important Role Insupporting
confidence: 88%
“…As reported earlier from our laboratory, exposing FLS to HT resulted in significantly reduced mRNA and protein levels of many pro-inflammatory genes that would otherwise be highly upregulated in response to IL-1β (4). We further demonstrated by electrophoretic mobility shift assays (EMSA) and western blot experiments that HT prevented IκB degradation and nuclear translocation of NF-κB in this cell type (4).…”
Section: Fibroblast-like Synoviocytes (Fls) Play An Important Role Insupporting
confidence: 79%
“…Western Blot Experiments-SDS-PAGE and Western blotting were carried out essentially as described (16). Proteins were made visible using RenaissancePlus (PerkinElmer Life Sciences) and Kodak BioMax MR films or the chemiluminescence detection device GeneGnome (Syngene, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…EMSA-Preparation of nuclear extract, execution of EMSA, and EMSA specificity control experiments have been described in detail on a number of occasions (16,19,20). In short, oligonucleotides resembling consensus binding sites for NF-B (5Ј-AGT TGA GGG GAC TTT CCC AGG C-3Ј), AP-1 (c-Jun) (5Ј-CGC TTG ATG AGT CAG CCG GAA-3Ј), and CRE (5Ј-AGA GAT TGC CTG ACG TCA GAG AGC TAG-3Ј)) were purchased from Promega (Promega, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation